2019
DOI: 10.1176/appi.ajp.2018.17121358
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Biomarkers for Treatment Response Prediction in Major Depressive Illness: A Meta-Analysis

Abstract: Objective: Reducing unsuccessful treatment trials could improve depression treatment. Quantitative analysis of the electro-encephalogram (QEEG) might predict treatment response, and is being commercially marketed for this purpose. The authors sought to (1) quantify the reliability of QEEG for response prediction in depressive illness and (2) identify methodological limitations of the available evidence. Method: The authors performed a meta-analysis of diagnostic accuracy for QEEG in depressive illness, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 118 publications
(164 reference statements)
3
129
0
1
Order By: Relevance
“…Second, and closely related to the above argument, even after decades of massive research efforts there is no evidence of robust neurobiological and genetic predictors of differential treatment response in depression 6–9 32. Biostatistics professor Dr Stephen Senn once stated: ‘Unless patient by treatment interaction exists, it is pointless looking for gene by treatment interactions’ 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, and closely related to the above argument, even after decades of massive research efforts there is no evidence of robust neurobiological and genetic predictors of differential treatment response in depression 6–9 32. Biostatistics professor Dr Stephen Senn once stated: ‘Unless patient by treatment interaction exists, it is pointless looking for gene by treatment interactions’ 33.…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial research efforts, no predictors of treatment success with ADs were found that were robust and reliable enough for use in clinical practice 6–9. Thus, much of the variance of the treatment outcome remains unexplained so far.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, while there are a number of promising EEG metrics associated with positive rTMS treatment outcomes in depressed patients, currently there is insufficient data for deployment of any of them in a standard clinical setting. Indeed, results of a recent meta-analysis underscore the fact that there is presently insufficient evidence to recommend use of EEG for guiding rTMS or other psychiatric treatment decisions at the present time [60]. As noted by the authors, several factors characterizing the currently published body of EEG biomarker studies may contribute, including under-publication of negative results, lack of out of sample validation, and insufficient direct replication of previous findings.…”
Section: Quantitative Eeg Analyses Utilizes Mathematical Transformatimentioning
confidence: 99%
“…Some medical entrepreneurs are trying to change that. In this month's issue, we cover a paper appearing in the American Journal of Psychiatry by Widge et al 1 examining the usefulness of quantitative electroencephalography (QEEG) for predicting treatment response in depression. This technology, which utilizes complex mathematical algorithms to analyze EEG waveforms, has been around for many years, but the advent of readily available powerful computers has led to a recent increase in efforts to market this approach to clinicians.…”
mentioning
confidence: 99%
“…But as Widge et al (and Zeier et al, with regard to pharmacogenetics) have shown, we're not there yet, and the “use of commercial or research‐grade QEEG methods in routine clinical practice would not be a wise use of health care dollars.” 1 Given the many potential demands on those scarce dollars, in psychiatry as well as in the rest of medicine, it's incumbent on all of us to be cautious in welcoming these new technologies into the clinic until their validity, and cost/benefit utility, are clear.…”
mentioning
confidence: 99%